Hábito alimentario y descripción morfológica de la larva de dos especies de pega-pega (Helcystogramma spp. y Lygropia tripunctata (Fabricius)) en boniato (Ipomoea batatas (L.) Lam.) - Alfredo Morales Rodríguez (Agrisost, 2015)
Alimentary habit and morphological description of the larva of two species of leaf folder (Helcystogramma spp. and Lygropia tripunctata (Fabricius)) of sweet potato (Ipomoea batatas L. Lam.) Too little are known about the majority of defoliators insects of the sweet potato, as its the case of lepidopterous Helcystogramma sp and Lygropia tripunctata. The objectives of present investigation are to know morphologic aspects and alimentary habit of the larva of these species. The work was done at Institute Research of Tropical Root (INIVIT). Insects were studied by direct observation in two fields of sweet potato. The larva of Helcystogramma sp has the head, three thoracic segments and three pairs of paws of black color, while the larva of L. tripunctata has the head of yellow color and its has the body green-bluish translucent. The larva of Helcystogramma sp glues the leaf with silk threads and when its feed leave the inferior epidermis or superior intact. L.tripunctata glues several leaf during its larval status and its does not eat the part of the leaf that it glues.